Unstructured play with active equipment enhances moderate-to-vigorous physical activity in children - Huu Tri, Nguyen; Tram, Nguyen Quoc; Thanh Minh, Trinh Thi; Thanh Trung, Nguyen (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study examined the impact of a daily 25-minute unstructured physical activity (PA) break on the PA levels of children aged 7–9 years. Recess periods provide valuable opportunities to boost PA and counteract sedentary behaviors, especially when active play equipment is available. In this randomized controlled trial, 71 children were allocated to either an experimental group (EG; n=39), which participated in daily 25-minute free play sessions with access to sports equipment, or a control group (CG; n=32) following standard recess protocols. Accelerometer measurements indicated a statistically significant increase (p<0.05) in moderate-to-vigorous PA (MVPA) in the EG relative to the CG, aligning with the World Health Organization’s 2020 guidelines on reducing sedentary behavior. These findings suggest that incorporating brief, unstructured PA breaks equipped with active play tools can enhance the effectiveness of school-based PA interventions and promote higher activity levels among children. Future research should explore the long-term benefits of such approaches.